" Huizenbouw in Hollandia". Veel Indische Nederlanders werken als arbeiders bij de huizenbouw of de wegenaanleg
" Huizenbouw in Hollandia". Veel Indische Nederlanders werken als arbeiders bij de huizenbouw of de wegenaanleg.